2022
DOI: 10.1071/cp21710
|View full text |Cite
|
Sign up to set email alerts
|

Insect detection from imagery using YOLOv3-based adaptive feature fusion convolution network

Abstract: Context Insects are a major threat to crop production. They can infect, damage, and reduce agricultural yields. Accurate and fast detection of insects will help insect control. From a computer algorithm point of view, insect detection from imagery is a tiny object detection problem. Handling detection of tiny objects in large datasets is challenging due to small resolution of the insects in an image, and other nuisances such as occlusion, noise, and lack of features. Aims Our aim was to achieve a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In the distortion-corrected wide-angle depth image of the downhole cable laying environment, perform the cable nameplate area selection operation, and use the SIFT feature descriptor operator to perform effective feature extraction on the area. After the feature extraction is completed, input it into the YOLOv3 network structure to detect the stickers on the cable [6], and combine it with the wide-angle depth image of the cable laying environment to obtain the depth value of the cable label in the wide-angle depth image of the cable laying environment, thereby completing the arm hand-eye calibration and camera internal parameter calibration operation. Based on the camera imaging principle, solve the coordinate position of the cable nameplate in the mechanical wall coordinate system.…”
Section: Accurate Identification and Detection Of Cable Nameplate Inf...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the distortion-corrected wide-angle depth image of the downhole cable laying environment, perform the cable nameplate area selection operation, and use the SIFT feature descriptor operator to perform effective feature extraction on the area. After the feature extraction is completed, input it into the YOLOv3 network structure to detect the stickers on the cable [6], and combine it with the wide-angle depth image of the cable laying environment to obtain the depth value of the cable label in the wide-angle depth image of the cable laying environment, thereby completing the arm hand-eye calibration and camera internal parameter calibration operation. Based on the camera imaging principle, solve the coordinate position of the cable nameplate in the mechanical wall coordinate system.…”
Section: Accurate Identification and Detection Of Cable Nameplate Inf...mentioning
confidence: 99%
“…thereby achieving binary thresholding of the cable nameplate gray image and effectively segmenting the cable nameplate image to obtain foreground and background information of the cable nameplate image (6). Cable nameplate text recognition based on OCR.…”
mentioning
confidence: 99%
“…The openness of the public research process is seen as vital for the development of next-generation phenotyping (Tripodi et al 2023). It is also required for the development of advanced weed or insect recognition cited in Australia (Amrani et al 2023;Mahmudul Hasan et al 2023), although in all such cases, the investment needed to scale these applications up will almost inevitably move the IP into the domains of the third classspecialist supplierbefore digital agriculture applications can be offered to farmers. Jackson and Cook (2023) illustrate the opportunities and challenges of pulling digital technologies into the livestock industry in Australia.…”
Section: Crop and Pasture Sciencementioning
confidence: 99%
“…2023). It is also required for the development of advanced weed or insect recognition cited in Australia (Amrani et al . 2023; Mahmudul Hasan et al .…”
mentioning
confidence: 99%
“…Many researchers [26,27] constructed databases by fixed pest collection devices and utilized detectors such as YOLOv5 for pest detection. In order to enhance the discrimination ability of detectors for multiple categories of pests, feature fusion [28,29] was considered for algorithmic improvement, and it was experimentally demonstrated that feature fusion is effective in improving detection accuracy. Classification-based methods [21][22][23] focused on the global features of images.…”
Section: Introductionmentioning
confidence: 99%